Saprahan Tradition: Exploring Local Wisdom as a Reflection of The Value of The Profile of Pancasila Students in West Kalimantan - Putri, Pratiwi Amalia; Alfarisi, Muhammad Adib (Edudeena : Journal of Islamic Religious Education, 2024)
Abstract: This research aims to examine the Saprahan Tradition, one of the cultures of the Malay community in West Kalimantan as a form of local wisdom. This tradition reflects the values of the Pancasila Student Profile, namely having noble character, global diversity, independence, working together, critical reasoning and creativity. This research uses a qualitative approach with ethnographic study methods to reveal the cultural values contained in the implementation of Saprahan and their relevance in forming student character in the Pancasila Student Profile. The research results show that the Saprahan Tradition is not only a cultural heritage, but also has adaptive capabilities in dealing with problems faced by human life. The values and norms of local wisdom in the Saprahan tradition become a form of kinship in the community's cultural space. Some of the values of the Pancasila Student Profile that are visible in the Saprahan Tradition are (1) Mutual Cooperation, visible in the togetherness of the community who work hand in hand in implementing the Saprahan Tradition; (2) Global Diversity, seen in cultivating the value of Unity by respecting differences in order to create a peaceful life; (3) Having noble character, seen in the practice of religious values such as a sense of solidarity, mutual respect and respect between religions, tribes, groups, and social responsibility and (4) Critical and creative reasoning, seen in the local wisdom values included in the curriculum and realized in learning materials. It is hoped that this research can provide implications and contribute to cultural preservation efforts while supporting the Pancasila Student Profile program in schools, especially in West Kalimantan.